Assessment of evaporative and photochemical effects on asphaltene profiling of a heavy fuel oil. Issue 2 (2nd April 2020) - Thompson, Joshua; Pietsch, Leshelle; Phillips, Michael; Lennard, Chris; Fuller, Stephen; Spikmans, Val
Abstract: Oil fingerprinting is concerned with determining the chemical profile of a spilled oil to determine its origin, whether that be a vessel, well or other source. Asphaltenes are typically discarded in this process even though they are considered refractory in comparison to the volatile fraction and have the ability to provide valuable information in oil fingerprinting. A heavy fuel oil was exposed to evaporative and photochemical conditions to determine if the asphaltene fraction and asphaltene profiling were influenced by weathering. It was found that although evaporative weathering had a strong effect on the volatile fraction of the oil, it had no influence on the asphaltene fraction, and profiling of the asphaltene fraction using previously published methods was still possible. When the oil was exposed to photo-oxidative conditions using natural sunlight, the mass of the asphaltene fraction increased significantly. Attenuated Total Reflectance - Fourier Transform Infrared (ATR-FTIR) analysis demonstrated that the oxygen level in the asphaltene fraction also increased with photochemical weathering compared to evaporative weathering alone. Even though the asphaltene fraction changed under photo-oxidative conditions, it could still be used for source determination using previously published ATR-FTIR and pyrolysis GC-MS methods for profiling of the asphaltene fraction.